Effects of sidewall opening areas on the performance of broiler chickens and the indoor climatic conditions of backyard poultry building - Jongbo, Ayoola Olawole (Acta Scientiarum. Animal Sciences, 2024)
Sidewall openings play an important role in the indoor conditions of livestock buildings. It influences airflow patterns, air velocity distribution at the animal-occupied zones and the illumination level in the naturally ventilated animal building. However, there is a paucity of information on the effects of sidewall opening areas on the performance of broiler chickens. Hence, this study investigated the effect of sidewall opening areas on the indoor condition and the body growth of broilers. Two buildings with different sidewall opening areas were developed with broiler chickens reared in them for 28 days. The results showed that air temperatures and relative humidity of the buildings were influenced by the outdoor temperature. The indoor air temperatures of the building exceeded the recommended thermal conditions (18 to 24ºC) for broiler chickens. Similarly, the temperature-humidity index of the building exceeded 21.0ºC recommended for broilers which could result in heat stress and poor performance of broiler chickens during extremely hot weather periods. It was also found in this study that broiler chickens could not perform optimally though they were fed ad libitum. Therefore, further studies are required to ascertain the impact of sidewall opening areas on broiler performance, behaviour and physiological responses.